Особливості епідемічного процесу вітряної віспи серед військовослужбовців південного регіону - Півник, В.М.; Рожков, А.А.; Тверезовський, М.В.; Петренко, В.А.; Тверезовський, В.М. (Актуальні проблеми транспортної медицини, 2011)
В публикации предоставленны результаты обзора заболеваемости ветряной оспой в военном коллективе, проведено определение ее актуальности для войск на современном этапе и обоснования проведения противоэпидемических мероприятий, их направленности и интенсивности. Since 2002 we’ve noticed enormous increase of ill military men for smallpox. The highest levels of sickness are marked among soldiers. We registered 1023 cases of smallpox in soldiersа протяжении. Among last one and sergeants it’s 92,8%, and 2,6% among officers and contract persons – 4,6% cases. In 2009 the level of disease in soldiers was as 30 as higher then in others types of persons. Before 2002 smallpox was noticed just as line cases. As it can be seen in annual dynamics of epidemical process there’s the main line. That’s the long period of season increase that can reach 311 days in its medial indicator and continues from January to Julу and from September to December. According to medial level – 176 days or 48% of year. Considering features of appointment of staff, the most effective antiepidemical action is prophylactic vaccination of recruits, anamnesis of last one having no data about smallpox.